Mitochondrial genome repositioning during the differentiation of the African trypanosome between life cycle forms is microtubule mediated. - Matthews, K; Sherwin, T; Gull, K (1995)
The cell cycle of the African trypanosome requires a precise orchestration of nuclear and mitochondrial genome (kinetoplast) positioning to ensure faithful segregation during division. The controls underlying these events must be subject to modulation, however, as the respective positioning of these organelles changes during the parasite's complex life cycle. We have studied mitochondrial DNA repositioning during differentiation between the trypanosome's bloodstream and procyclic form. We have found that repositioning occurs simultaneously with the DNA replication phase of the cell cycle of the differentiating parasite. Furthermore, we demonstrate, at the cell and individual microtubule level, that this organelle repositioning is achieved via microtubule-dependent processes. Our results have implications for the control of cell differentiation and division in African trypanosomes.